EFL Students’ Perceptions of the Effective English Teacher Characteristics - Tatipang, Devilito Prasetyo; Manuas, Maissy J.; Wuntu, Ceisy Nita; Rorintulus, Olga A.; Lengkoan, Fergina (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
This study aimed to analyze EFL students' perceptions of the characteristics of the English language teachers and find out whether there is any difference in the student perceptions of the characteristics of effective English teachers based on gender. This study is quantitative. The research design used in this study is the descriptive and comparative research design. The descriptive design was used because the purpose is to examine and describe the students' perceptions of the characteristics of effective English language teachers. The questionnaires also consist of the respondents' profiles such as gender and 24 modified items of questions regarding students' perceptions of the characteristics of effective English teachers.  This study involved 120 respondents from grade 11 of science, social, and Language class. The results of this study showed that students' perceptions of the characteristics of effective English teachers were found to be high involvement since the mean score was 3.08. The result of this study also found that there was no significant difference in the EFL Students' perceptions of the characteristics of effective English teachers based on gender since the result got p= 0.018. Another result of this study found that socio-affective skills are the distinctive characteristic that teachers must have to call an effective English teacher since the mean score was 3.45.